Epidemiologic and Health Economic Evaluation of Cervical Cancer Screening in Rural China - Zhao, Fei (Asian Pac J Cancer Prev, 2020)
BACKGROUND: Cervical cancer is preventable and curable by detected early and managed effectively. To explore the most economical and effective cervical cancer screening strategies would lay a solid foundation for reducing the health and economic burden of cervical cancer. METHODS: A Markov model was established for a cohort of 100,000 female to simulate the natural history of cervical cancer. 18 screening strategies were estimated including careHPV, Thin prep cytologic (TCT), Visual inspection with acetic acid/ Lugol’s iodine (VIA / VILI), careHPV in series with VIA / VILI, careHPV in series with TCT, three methods parallel connection every 1, 3, 5 years respectively. Model outcomes included cumulative risk of incidence and death of cervical cancer, quality-adjusted life years (QALYs), cost-effectiveness ratios (CERs), incremental cost-effectiveness ratios (ICERs), cost-utility ratios (CURs) and benefits. RESULTS: According to the results of epidemiological analysis, careHPV similar to the parallel connection every 1 year achieved highest epidemiological effects via reducing the cumulative risk of onset and death by more than 98 %. In health-economic terms, CER among all the screening strategies ranged from -756.34 to 113040.3 Yuan per year and CUR ranged from -169.91 to 11968.27 Yuan per QALY. The benefit ranged from -1629 to 996 Yuan. The incremental cost-effectiveness analysis showed that three methods in parallel every 1 year, TCT every 1 year, VIA/VILI every 1, 3, 5 years and careHPV every 5 years were dominant strategies. CONCLUSION: Considering the economic and health benefits of all the strategies, our results suggested careHPV every 3 or 5 years and VIA/VILI every 1 or 3 years eventually were more appropriate as screening methods in rural China.